Navigated percutaneous screw fixation of the pelvis with O-arm 2: two years’ experience - Gianluca Ciolli; Daniele Caviglia; Carla Vitiello; Salvatore Lucchesi; Corrado Pinelli; Domenico De Mauro; Amarildo Smakaj; Giuseppe Rovere; Luigi Meccariello; Lawrence Camarda; Giulio Maccauro; Francesco Liuzza (Medicinski glasnik, 2020)
Aim: To evaluate the case series of the patients operated with percutaneous fixation by the navigation system based on 3D fluoroscopic images, to assess the precision of a surgical implant and functional outcome of patients. Methods: A retrospective study of pelvic ring fractures in a 2-year period included those treated with the use of the O-Arm 2 in combination with the Stealth Station 8. Pelvic fractures were classified according to the Tile and the Young-Burgess classification. All patients were examined before surgery, with X-rays and CT scans, and three days after surgery with additional CT scan. The positioning of the screws was evaluated according to the Smith score, the outcome with the SF-36. Results: Among 24 patients 18 were with B and six with C type fracture according to Tile, while eight were with APC, 10 LC, and six with VS type according to Young-Burgess classification. All patients were treated in the supine position, except two. A total of 41 iliosacral or transsacral screws and five anterior pelvic ring screws were implanted. The medium surgical time per screw was 41 minutes. There was a perfect correspondence of screw scores value from post-operative CT and intraoperative fluoroscopy. The mean screw score value was 0.92. There were no cases of poor positioning. The median follow-up was 17.5 months. The patients were satisfied with their health condition on SF-36. Conclusion: The use of the O-arm guarantees great precision in the positioning of the screws and reduced surgical times with excellent clinical results in patients.
Keywords: 3D-fluoroscopic navigation; fragility fracture of pelvis; iliosacral fixation; O-arm Stealth Station S8; pelvic ring fractures